Organizational antecedents and capabilities for sustainable supply chain management in developing economies: The case of Colombian focal firms (2016)
Knowledge about sustainable supply chain practices in developing economies is still lacking. Consequently, this research empirically explores the organizational antecedents and the implementation of Sustainable Supply Chain Management (SSCM) practices for a purposeful sample of focal firms in Colombia. A semi-structured qualitative research design is followed. This study contributes to the development of SSCM theory by providing empirical grounds for understanding the nature of these practices and the extent of their implementation in a particular industrial context, as well as by assessing whether and how they affect the focal firms’ competitiveness. Additionally, the main results suggest that environmental and social responsibilities are increasingly important issues for the stakeholders of focal companies in emergent economies.